Body mass index, waist circumference, waist-hip ratio, and glucose intolerance in Chinese and Europid adults in Newcastle, UK. Issue 2 (April 1997) - Unwin, N; Harland, J; White, M; Bhopal, R; Winocour, P; Stephenson, P; Watson, W; Turner, C; Alberti, K G
Abstract : OBJECTIVE: To compare the prevalence of glucose intolerance (impaired glucose tolerance and diabetes), and its relationship to body mass index (BMI) and waist-hip ratio in Chinese and Europid adults. DESIGN: This was a cross sectional study. SETTING: Newcastle upon Tyne. SUBJECTS: These comprised Chinese and Europid men and women, aged 25-64 years, and resident in Newcastle upon Tyne, UK. MAIN OUTCOME MEASURES: Two hour post load plasma glucose concentration, BMI, waist circumference, and waist-hip ratio. METHODS: Population based samples of Chinese and European adults were recruited. Each subject had a standard WHO oral glucose tolerance test. RESULTS: Complete data were available for 375 Chinese and 610 Europid subjects. The age adjusted prevalences of glucose intolerance in Chinese and Europid men were 13.0% (p = 0.04). Mean BMIs were lower in Chinese men (23.8 v 26.1) and women (23.5 v 26.1) than in the Europids (p values < 0.001), as were waist circumferences (men, 83.3 cm v 90.8, p < 0.001; women, 77.3 cm v 79.2, p < 0.05). Mean waist-hip ratios were lower in Chinese men (0.90 v 0.91, p = 0.02) but higher in Chinese women (0.84 v 0.78, p < 0.001) compared with Europids. In both Chinese and Europid adults, higher BMI, waist circumference, and waist-hip ratio were associated with glucose intolerance. CONCLUSIONS: The prevalence of glucose intolerance in Chinese men and women, despite lower BMIs, is similar to or higher than that in local Europid men and women and intermediate between levels found in China and those in Mauritius. It is suggested that an increase in mean BMI to the levels in the Europid population will be associated with a substantial increase in glucose intolerance in Chinese people.